Rapid Identification of Helicoverpa armigera and Helicoverpa zea (Lepidoptera: Noctuidae) Using Ribosomal RNA Internal Transcribed Spacer 1. Issue 1 (29th October 2015) - Perera, Omaththage P.; Allen, Kerry C.; Jain, Devendra; Purcell, Matthew; Little, Nathan S.; Luttrell, Randall G.
Abstract : Rapid identification of invasive species is crucial for deploying management strategies to prevent establishment. Recent Helicoverpa armigera (Hübner) invasions and subsequent establishment in South America has increased the risk of this species invading North America. Morphological similarities make differentiation of H. armigera from the native Helicoverpa zea (Boddie) difficult. Characteristics of adult male genitalia and nucleotide sequence differences in mitochondrial DNA are two of the currently available methods to differentiate these two species. However, current methods are likely too slow to be employed as rapid detection methods. In this study, conserved differences in the internal transcribed spacer 1 (ITS1) of the ribosomal RNA genes were used to develop species-specific oligonucleotide primers that amplified ITS1 fragments of 147 and 334 bp from H. armigera and H. zea, respectively. An amplicon (83 bp) from a conserved region of 18S ribosomal RNA subunit served as a positive control. Melting temperature differences in ITS1 amplicons yielded species-specific dissociation curves that could be used in high resolution melt analysis to differentiate the two Helicoverpa species. In addition, a rapid and inexpensive procedure for obtaining amplifiable genomic DNA from a small amount of tissue was identified. Under optimal conditions, the process was able to detect DNA from one H. armigera leg in a pool of 25 legs. The high resolution melt analysis combined with rapid DNA extraction could be used as an inexpensive method to genetically differentiate large numbers of H. armigera and H. zea using readily available reagents.